Pengaruh Social Media Marketing dan Environmental Knowledge Terhadap Green Purchase Intention dengan Customer Trust Sebagai Variabel Mediasi pada Generasi Z di Sleman - Dita Kusuma Sari; Andriya Risdwiyanto (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to determine and analyze the effect of Social Media Marketing and Environment Knowledge on Green Purchase Intention with Customer Trust as a Mediating Variable in Generation Z in Sleman. This study uses quantitative research methods using a questionnaire. The population in this study is Generation Z in Sleman, Yogyakarta Special Region who consume drinking water in gallons of the Aqua brand. The data collection technique used purposive sampling technique. The sample in this study amounted to 95 respondents. The analysis method used in this research is Partial Least Square (PLS). The results showed that social media marketing has a significant direct effect on green purchase intention, environmental knowledge has a significant direct effect on green purchase intention, social media marketing has a significant direct effect on customer trust, environmental knowledge has a significant direct effect on customer trust. Meanwhile, customer trust does not have a significant direct effect on green purchase intention. In the mediation test, customer trust is able to mediate social media marketing on green purchase intention and customer trust is able to mediate environmental knowledge on green purchase intention.